Bacteria-mediated cancer therapy: A versatile bio-sapper with translational potential - Luo, Miao; Chen, Xiaoyu; Gao, Haojin; Yang, Fan; Chen, Jianxiang; Qiao, Yiting (Frontiers in Oncology, 2022)
Bacteria are important symbionts for humans, which sustain substantial influences on our health. Interestingly, some bastrains have been identified to have therapeutic applications, notably for antitumor activity. Thereby, oncologists have developed various therapeutic models and investigated the potential antitumor mechanisms for bacteria-mediated cancer therapy (BCT). Even though BCT has a long history and exhibits remarkable therapeutic efficacy in pre-clinical animal models, its clinical translation still lags and requires further breakthroughs. This review aims to focus on the established strains of therapeutic bacteria and their antitumor mechanisms, including the stimulation of host immune responses, direct cytotoxicity, the interference on cellular signal transduction, extracellular matrix remodeling, neoangiogenesis, and metabolism, as well as vehicles for drug delivery and gene therapy. Moreover, a brief discussion is proposed regarding the important future directions for this fantastic research field of BCT at the end of this review.